Study of Expression of Sugarcane Sucrose Transporter cDNA in Yeast - Slameto, Slameto; Sugiharto, Bambang; Basuki, Nur; Sulistyowati, Liliek (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Studies in transgenic sugarcane (Saccharum officinarum L.) demonstrated that sucrose transporter (SUT) genes were essential in sucrose translocations. Sucrose transporter gene isolated from sugarcane were designated as SoSUT1 and SoSOSUT2 respectively as encode protein of 518 and 747 amino acids. The genes were constructed into plasmid pYES2 for SoSUT1, and pYX112 for SoSOSUT2. cDNA SoSOSUT2 had also constructed into plasmid pBIN-At-GFP which was possible to trace the gene inserted. The constructed plasmid was transformed into yeast (Saccharomyces cerevisiae) and grown in minimal medium (SD–urasil) as selection medium. The transformed colony was confirmed using PCR. The functional expression was studied by growing yeast in YPD medium with 2% Sucrose, then the sucrose uptake was measured in number interval time using resorcinol method. The result showed that yeast INVSc1-pYES2-SoSUT1 and BF264- pYX112-SoSOSUT2 had higher ability in sucrose transport compared to the control-INVSc1 for SoSUT1 and control-BF264 for SoUT2. Moreover, the result showed that SoSUT1 had higher ability to transport sucrose than SoSOSUT2. Confocal microscope observation showed that transformation gene SoSOSUT2 was successful, which was indicated by green exposure of GFP protein.Keyword: sugarcane, sucrose transporter, yeast